ENABLING SCAN-TO-BIM WORKFLOW FOR HERITAGE CONSERVATION AND MANAGEMENT PROCESS - R. Angeloni; C. Mariotti; L. Petetta; L. Coppetta (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
The paper stresses the potential of digital technology in the field of Cultural Heritage (CH), focusing on Architectural Heritage (AH) conservation and management process. It presents a workflow based on non-parametric automatic 3D modeling and Industry Foundation Classes (IFC) authoring to combine geometry and semantic information. The goal of such a methodology is to overcome time-consuming manual tasks that still limit the Historical Building Information Modelling (HBIM), which nevertheless proves to be one of the most effective digital tools for the conservation and management of AH in the medium to long term. The proposed workflow consists of five steps: the 3D survey campaign and raw data processing, the semantic annotation of images according to different information layers, the annotation transfer from images to the point cloud representing the studied architecture, the obtained Point Cloud Information Model (PCIM) automatic segmentation and 3D mesh wrapping, and finally the IFC generation for the HBIM representation. This unconventional digital chain was tested to support the knowledge representation of Villa Leonardi, an historical house in the Marche Region (Italy). The final output is a 3D model of the building, automatically processed from digital survey data, and semantically enriched thanks to the material consistency and decay analysis carried out and annotated on spherical panoramas. The effectiveness of this approach was proven in the conservation project for the façades of the house: enriched data on materials and decay supported an action plan of restoration works, which was then recorded in the HBIM model, thus permitting time and cost control.